Kinerja Pegawai Berdasarkan Kompetensi Kerja, Motivasi Kerja, dan Komitmen Kerja - Susanti, Febsri; Nora, Fitri (JURNAL PUNDI, 2025)
This study aims to determine the effect of work competence, work motivation, and work commitment on the performance of the employees of the Secretariat of DPRD Kota Pariaman as many as 49 people. The research method is by collecting data through distributing questionnaires to the entire population which can be used for analysis purposes. This hypothesis testing is done by using multiple linear regression data analysis techniques. The results of the data analysis show that from the three independent variables, the results of hypothesis testing are obtained: Job competence has a significant effect on the performance variable (dependent variable). Furthermore, work motivation variable has a significant effect on performance. And the work commitment variable has a significant effect on performance. Likewise with the simultaneous test, the three independent variables also affect the performance as the dependent variable. The results of the hypothesis testing found that the magnitude of the influence of work competence, work motivation and work commitment to performance was 75.8%. While the rest (100% - 75.8% = 24.2%) is influenced by other variables outside this regression model